Validation of the Functional Model of Social Media Networks in the Labor and Teachers’ Social Movements in Iran (2015–Present) - Moradi , Fershteh; Malekiyan, Nazanin; Hashem Zehi, Nowruz; Niroomand, Leila (Digital Transformation and Administration Innovation, 2024)
The study aimed to validate a comprehensive functional model of social media networks in shaping awareness, mobilization, and democratic engagement within the social movements of Iranian teachers and workers from 2015 onward. This research employed a mixed-methods sequential design, integrating qualitative and quantitative approaches to ensure conceptual depth and empirical precision. In the qualitative phase, semi-structured interviews were conducted with 15 experts in communication, political science, journalism, and union activism using purposive and snowball sampling until data saturation. Thematic analysis following the Attride-Stirling network approach identified three levels of themes—basic, organizing, and global—leading to the conceptual model. The quantitative phase involved 400 participants from teacher and worker movements, selected through random sampling. A questionnaire derived from the qualitative themes was validated using content validity indices (CVI and CVR), Cronbach’s alpha, and composite reliability. Statistical analyses, including t-tests and factor analyses, were performed using SPSS to test the model’s structure and reliability. Descriptive and inferential analyses confirmed that all latent variables—awareness and information dissemination, mobilization and organizing, collective power, transformation of social and cultural structures, and democratic engagement—were positively and significantly correlated. Model fit indices (AVE = 0.62–0.69; CR = 0.79–0.93) indicated high convergent validity and internal consistency. The highest explanatory power appeared in mobilization and organizing (R² = 0.657), while awareness and information dissemination recorded the highest mean (M = 3.94). The validated model demonstrated that social media act as central mechanisms of awareness, solidarity, and participation in Iranian professional movements. The study confirmed that social media networks function as multidimensional infrastructures of communication, coordination, and democratization, transforming professional activism into networked, participatory, and connective forms of collective action in Iran’s socio-political landscape.